Timeline Analysis of Corrective and Prevention Action of Completion by Pharmaceutical Wholesalers in the Framework of Good Distribution Practices Certification Year 2020-2022 - Lili Damayanti; Dumilah Ayuningtyas; Teti Hastati (Journal of Social Research, 2023)
The mandatory implementation of Good Distribution Practices (GDP) for Pharmaceutical Wholesalers can secure drug distribution channels from counterfeiting and misuse of drugs by the public. One of the important things in accelerating the GDP Certification process is the stage of completing Corrective and Preventive Action (CAPA) by Pharmaceutical Wholesalers. The purpose of this study is to analyze the timeline for the completion of CAPA by Pharmaceutical Wholesalers in the framework of GDP Certification in 2020 – 2022 so that an overview of Pharmaceutical Wholesalers’ ability and readiness to implement the GDP Certification policy as a business licensing standard is obtained. This study used a quantitative approach with descriptive analysis methods, using GDP Certification data from the Indonesian FDA. The results showed that the fastest average time to complete CAPA by Pharmaceutical Wholesalers was in 2022, which was 31 working days with 3 submissions, followed in 2021 by 41 working days with 4 submissions, while the longest CAPA completion time was in 2020 for 71 working days with 5 submissions. In general, this has met the provisions of the Indonesian FDA Regulation Number 25 of 2017, but if you refer to the latest regulations, namely Government Regulation Number 5 of 2021 and the Indonesian FDA Regulation Number 10 of 2021, the average time for CAPA completion by Pharmaceutical Wholesalers in 2020-2022 still does not meet the requirements. The recommendation from this study is that it is necessary to carry out training, technical guidance, or assistance to improve the ability and readiness of Pharmaceutical Wholesalers so that the implementation of GDP certification according to the latest regulations can be fulfilled immediately.